Investigation of the molecular ordering and charge transport of circular oligomer / fullerene complexes for solar cell applications - Koçak, Olkan (My University, 2019)
GÜNEŞ PİLİ UYGULAMALARI İÇİN DAİRESEL OLİGOMER / FULLEREN KOMPLEKSLERİNİN MOLEKÜLER DÜZEN VE YÜK TAŞINIMLARININ İNCELENMESİBu tez çalışması organik fotovoltaik cihazlarda solar radyasyonun elektriksel güce dönüşümünün gerçekleştiği aktif katman için alternatif bir yapısal mimarinin teorik karakterizasyonunu ele almaktadır. Yığın heteroeklem morfolojisine alternatif olarak ev sahibi / konuk tipimoleküler kompleksleri-fulleren türü elektron akseptörü malzemeleri sarmalayan π-konjuge dairesel oligomer elektron donörü yapılar-incelenmiştir. Bu yapıların morfolojik özellikleri, donör ve akseptör bölgelerinde yük taşınım özellikleri ve donör/ akseptör arayüzünde yük ayrışması/ geribirleşmesi özellikleri hesaplanmıştır. Bu tür süreclerin temel anlamda anlaşılabilmesi için C60@[10]CPP, C70@[11]CPP ve C70@[3]CPPA olmak üzere üç farklı prototip yapı ele alınmıştır. Komplekslerin katı hal paketlenme durumlarının arayüz morfolojisi, yük taşınım özellikleri ve malzemelerin elektronik performansları üzerinde etkisinin büyük olduğu görülmüştür.Yük taşınım simülasyonlarından deşik mobilitesi için 10-3 – 10-1 cm2/ Vs, elektron mobilitesi için 10-5 – 10-3 cm2/ Vs mertebesinde değerler elde edilmiştir. “Time domain drift diffusion” modeli ile gerçekleştirilen nümerik hesaplamalarla 1 güneş biriminde aydınlatma altında güç dönüşüm verimliliklerinin yaklaşık %10 mertebesinde olabilecekleri önerilmiştir.

INVESTIGATION OF THE MOLECULAR ORDERING AND CHARGE TRANSPORT OF CIRCULAR OLIGOMER / FULLERENE COMPLEXES FOR SOLAR CELL APPLICATIONSThis thesis deals with the theoretical characterization of an alternative structural architecture for the active layer in which the conversion of solar radiation to electrical power occurs in organic photovoltaic devices. Host/ guest type structural molecular complexes - circular π -conjugated nanohoop electron donor encapsulates an electron acceptor fullerene – are investigated as an alternative to the bulk heterojunction morphology. Morphological properties of these structures, charge transport properties in donor and acceptor domains and charge separation/ recombination properties at donor/ acceptor interface are calculated. In order to understand the fundamentals of these processes; three different prototype structures are considered: C60@[10]CPP, C70@[11]CPP and C70@[3]CPPA. It has been found that the solid state packing conditions of the complexes have a significant effect on the interface morphology, charge carrying properties and electronic performance of the materials. From charge transport simulations, values in the range of 10-3 - 10-1 cm2/ Vs for hole mobility and 10-5 - 10-3 cm2/ Vs for electron mobility have been calculated. Power conversion efficiency of ~10% has been offered from time domain drift diffusion model under 1 sun illumination.
Keywords: charge-transport; Dairesel oligomer; efficiency; fulleren; fullerene; host–guest; mobilite; mobility; nanohoops; organic photovoltaics; organik fotovoltaikler; verim; yük-taşınımı Circular oligomers